PENGARUH MODEL PEMBELAJARAN TEACHING GAMES FOR UNDERSTANDING (TGFU) TERHADAP MINAT BELAJAR PENJAS - Hasmarita , Sony (STKIP Pasundan, 2018)
The objectives to be achieved in this study are to find out the effect of the Teaching Games For Understanding (TGFU) learning model on the learning interests of student education in Mts Al-Hikmah Cibatu. The method that I use in this research is descriptive method through the correlation approach with a measuring instrument using a questionnaire. The questionnaire used was a closed questionnaire. The population and sample used were all grade VII students in Mts Al-Hikmah Cibatu, amounting to 64 taken from 2 classes of people and the sample was taken using proportional sampling technique. The sample that will be used in this research are 30 people consisting of 15 groups of Teaching Games For Understanding (TGFU) learning models and 15 people from conventional learning groups. Based on the results of research conducted by the author and calculation and analysis of data from the measurement results, then in this section the authors can put the following conclusions: Group A given the treatment model of teaching Teaching Games For Understanding (TGFU) gives a greater and significant effect compared to the group B was given the treatment of conventional learning models with different results of physical education interest (3.23> 1.68) in Mts Al-Hikmah Cibatu.